Media discourses of nation and cultural differences: a case study of Westdeutscher Rundfunk - Krtalić Muiesan, Iva (Sveučilište u Zadru., 2019)
Gerrmany is a country of migration and continues to be so, increasingly becoming a society of diverse ethnic and cultural identities. Today, over one fifth of its inhabitants have a so-called migration background, defined either as having migrated themselves or having at least one parent who has migrated to Germany. In institutional politics, or in the media, this reality is, however, often represented in a fragmented, belated, or even contradictory manner. At the same time, ways of responding to and “managing” difference within the territorial borders of the nation-state remain crucial concerns in the approaches to the questions of nation and citizenship. The thesis unlocks the régimes of truth that construct the discourses of the German society, identity, or belonging, identifying some of the core “nodal points” of these discourses, among them the terms multiculturalism, integration, tolerance, and cosmopolitanism. The thesis unpacks some of the concepts of the media discourses on “difference” and locates the points where they crack and rupture, pointing to the intersections of power and knowledge, and the shifting historical conditions that provide the horizon for their construction. The analysis is focused on a set of broadcasts specifically dedicated to multicultural life: Funkhaus Europa, a radio station within the biggest public service broadcaster in Germany, the Westdeutscher Rundfunk (WDR), established with the purpose of reflecting the cultural diversity in the country, and the thematic week dedicated to tolerance, organized by the German public service broadcasters in 2014. Njemačka je danas zemlja obilježena migracijom, pretvarajući se sve više u društvo raznolikih etničkih i kulturnih identiteta. Preko petine njezinih stanovnika ima takozvanu „migracijsku pozadinu“, što znači da su ili sami uselili ili potječu iz useljeničkih obitelji. Useljavanje u Njemačku kontinuirano traje od šezdesetih godina 20. stoljeća, a čak kad bi useljavanje odjednom i posve prestalo, broj ljudi „migracijske pozadine“ ...